A Comparative Study On Indonesian And English Acknowledgement Used In Undergraduate Theses - Aditama, Madya Giri, Drs. Agus Wijayanto M.A., Ph.D, Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
The objective of the research is to analyze the Generic Structure of Acknowledgement in Indonesian and English Undergraduate Thesis Acknowledgement. The type of the research of the study is descriptive comparative. The data collecting method which the writer uses is documentation method, where the samples take 50 English acknowledgements and 50 Indonesian acknowledgements which chosen randomly and analyzed according to Hyland's (2004) and Al-Ali's (2006) generic structure of Acknowledgement theory. The results of this research show that in Reflecting Move, Indonesian Acknowledgement data got 2% and English data 0%, then it is also reveal that the most prevalent move in written both of English and Indonesian acknowledgements derive from Thanking Moves that is Thanking God, Presenting Participants and Thanking for Academic Assistance both Indonesian and English got 100%, in Thanking for Resources English 44% and Indonesian 28%, and thanking for Moral support English 86% while Indonesian 100%. The last move is Announcing Move which consists of Accepting Responsibility where English 68% and Indonesian 48%, and Dedicating the Thesis where both English and Indonesian got 0%. This study also discovers that there are some similarities and differences between English and Indonesian acknowledgements.